The Role of the Religious Leaders in Peace Building in Sri Lanka in the Aftermath of War - Dhammajothi, M. (My University, 2011)
The proposed theme for paper presentation and discussion directly shows the urgency of establishing peace building process in the aftermath of the prolonged ruthless wars in some Asian countries. This urgency is strongly felt in Sri Lanka, which has commenced breathing somewhat freely, without dark shadows of fears and dangers looming around. Nearly three decades of suffering is more than enough to drive sanity into all-whether they are victims or victimizers to realize that peace is something not only to be wished for and cherished, but something that should be fostered, protected and preserved for the good, benefit and happiness of the present as well as for the good benefit and happiness of the posterity. However, experience shows that peace is very elusive and becomes sustainable only if the ground situation is properly prepared for it. We have had patches of peace in our recent history regularly punctuated by breaches of peace, sometimes on most flimsiest grounds. This shows how fragile peace is and therefore, this also serves as a warning for us to handle peace with utmost care. Now, we as the religious leaders who have undertaken this onerous task of facilitating the fostering and sustenance of this peace which at the moment is utterly ‘crisp’ as it were and even a mere slip of the tongue could shatter it. This perhaps is because peace has not dawned but ‘imposed’ as it were on the people. Peace is something that cannot be really imposed if it is to last long and also if it is to be constructive and beneficial. everyone should be made to feel that they all are living in peace: that all are free to talk, move about, express views , exchange ideas, engage in disputation and arriving at a amicable solutions. All should be made to feel and experience that they are not looked at with suspicion but considered sons and daughters sisters and brothers of the nation.